2022
DOI: 10.1287/orsc.2021.1483
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gaps: How Organization Design Shapes the Sourcing of Inventions

Abstract: An important problem for many firms is sustaining their rate of innovation by launching new products on an ongoing basis. Accordingly, firms need to replenish their innovation pipelines with new inventions as existing inventions are weeded out or reach fruition. The replenishment can be done through internally generated inventions or through externally sourced inventions via licensing, alliance, or acquisition modes. Drawing on incentives- and knowledge-based views of the firm, we consider the difference in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…First, I highlight the importance of considering the effect of R&D team design on innovation. Organizational design shapes how its employees learn and absorb new knowledge (Clement & Puranam, 2018; Eklund & Kapoor, 2022; Karim & Kaul, 2015). In particular, understanding the critical role of collaborative teams in driving innovation within firms (Edmondson & Harvey, 2018; Mortensen & Haas, 2018; Singh & Fleming, 2010; Taylor & Greve, 2006; Teodoridis, 2018; Wuchty et al, 2007), scholars have explored how different ways of designing teams affect organization outcomes (Choudhury & Haas, 2018; Hoisl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…First, I highlight the importance of considering the effect of R&D team design on innovation. Organizational design shapes how its employees learn and absorb new knowledge (Clement & Puranam, 2018; Eklund & Kapoor, 2022; Karim & Kaul, 2015). In particular, understanding the critical role of collaborative teams in driving innovation within firms (Edmondson & Harvey, 2018; Mortensen & Haas, 2018; Singh & Fleming, 2010; Taylor & Greve, 2006; Teodoridis, 2018; Wuchty et al, 2007), scholars have explored how different ways of designing teams affect organization outcomes (Choudhury & Haas, 2018; Hoisl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In broad terms, an organization's structure encompasses the choices made along four dimensions: task division, task allocation, provision of incentives, and provision of information (Galbraith, 1973;Puranam, Alexy, and Reitzig, 2014). These choices can significantly impact the way an organization's knowledge is stored, shared internally, and applied toward innovation (Denrell, Fang, and Winter, 2003;Eklund, 2022). A range of studies have demonstrated how structural features such as hierarchy (Gavetti, 2005;Csaszar, 2013;Lee, 2022), task differentiation (Dougherty, 1992;Burton and Obel, 2004), and the incentives of employees (Lerner and Wulf, 2007;Manso, 2011) may affect an organization's innovation outcomes.…”
Section: Theorymentioning
confidence: 99%
“…An organization's structure determines where its knowledge is located, the pathways along which knowledge flows internally, as well as the incentives of its employees to acquire, use and share knowledge (Argyres, Rios, and Silverman, 2020;Lee, 2022). Several studies have demonstrated that organizations' innovation outcomes are closely linked to their structures (Argyres and Silverman, 2004;Ter Wal et al, 2020;Eklund, 2022), which also impacts the value they are able to derive from external partnerships (Arora, Belenzon, and Rios, 2014;Sytch, Wohlgezogen, and Zajac, 2018;Eklund and Kapoor, 2022). However, the knowledge firms seek to access via partnerships is embedded within their partners' organizations rather than their own, and the impact of their partners' structures in shaping their access to this knowledge remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Early research highlights that a firm solves a problem using both internally generated and externally sourced knowledge (Cassiman and Veugelers, 2006). Building on related research, we posit that the extent to which intrafirm network affects a firm’s new knowledge search is determined by the firm’s external alliance number (Eklund and Kapoor, 2021).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%